Corner of Market and Post. - Unknown:::Creator::::::::::::
Written on verso: Corner of Market and Post. Photograph shows the Home Union building. The Home Union Store was located on the first floor and sold general merchandise, and the second floor housed the Verein Eintracht Hall.